2012
DOI: 10.1002/app.38642
|View full text |Cite
|
Sign up to set email alerts
|

Rubber‐toughened PLA blends with low thermal expansion

Abstract: In this study, poly (lactic acid) (PLA) blended with various rubber components, i.e., poly (ethylene‐glycidyl methacrylate) (EGMA), maleic anhydride grafted poly(styrene‐ethylene/butylene‐styrene) triblock elastomer (m‐SEBS), and poly(ethylene‐co‐octene) (EOR), was investigated. It was observed that EGMA is highly compatible due to its reaction with PLA. m‐SEBS is less compatible with PLA and EOR is incompatible with PLA. Electron microscopy (SEM and TEM) revealed that a fine co‐continuous microlayer structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 34 publications
3
41
0
1
Order By: Relevance
“…However, diffraction peaks of SEBS‐g‐MA are shifted to 9.69° and 28.85° in PLSE10, which may be due to polar‐polar interaction, ie, interaction between carbonyl groups of PLA and anhydride groups of SEBS‐g‐MA. Similar interaction was also observed by Jiang et al in PLA/SEBS‐g‐MA blend systems.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, diffraction peaks of SEBS‐g‐MA are shifted to 9.69° and 28.85° in PLSE10, which may be due to polar‐polar interaction, ie, interaction between carbonyl groups of PLA and anhydride groups of SEBS‐g‐MA. Similar interaction was also observed by Jiang et al in PLA/SEBS‐g‐MA blend systems.…”
Section: Resultssupporting
confidence: 87%
“…Sangeetha et al reported that impact strength was higher in PLA/SEBS‐g‐MA blends than that in PLA/SEBS, which may be due to the interaction between maleic anhydride groups in SEBS‐g‐MA and carbonyl groups of PLA. SEBS‐g‐MA copolymer is used to toughen many polymers such as polypropylene (PP), high density polyethylene, nylon‐6, nylon‐6,6 and PLA . Yoo et al reported that SEBS‐g‐MA is an effective impact modifier for PP/PLA blends.…”
Section: Introductionmentioning
confidence: 99%
“…12 A comprehensive review on toughening of PLA was made by Anderson et al 13 To have enhanced interactions between the materials and fine dispersion of the impact modifier, chemically complementary groups are preferred in the rubber structure for reactive blending. 16 In that study, E-GMA was compared with maleic anhydride grafted poly(styrene-ethylene/butylene-styrene) triblock elastomer (m-SEBS), and poly(ethylene-co-octene) (EOR). This leads to the utilization of glycidyl methacrylate (GMA) copolymers in PLA blends.…”
Section: Introductionmentioning
confidence: 99%
“…We recently proposed a substantial approach to the design of polymer blends with low CLTE values . The large reduction in CLTE is not based on the addition of a low‐thermal‐expansion filler to suppress bulk expansion, but on the fine control of the micromorphology of the polymer blend.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has also been observed by Ono et al and Kim et al in polypropylene/elastomer systems. This approach enabled the design of polymer materials with improved dimensional stability and impact resistance …”
Section: Introductionmentioning
confidence: 99%